Impact of Multiple-choice and Essay-based Assessments on Academic Performance and Stress Levels among Medical Students: A Cross-sectional Study - Tanya Chauhan; Shazia Hasan; Gyan Vardhan; Shubham Jhanwar; Gita Negi; Manisha Bisht; Shailendra Handu (Journal of Medical Evidence)
Background: Balancing classroom instruction and examinations poses challenges in education, particularly in diverse student populations, necessitating educational reform and assessment strategies to mitigate stress. Medical education, like other fields, requires both knowledge acquisition and practical application, yet reliance on internet resources may exacerbate stress and hinder academic performance. Assessment tools in medical education vary based on the skills being evaluated, with written formats such as multiple-choice questions (MCQs) and essay-based questions (EBQs) used for cognitive assessments. This study compares MBBS students’ performance and stress levels in pharmacology examinations using MCQs and EBQs. Aim: To compare the performance and level of stress in the MBBS students after going through multiple choice questions and essay-based examination pattern. Methods: A cross-sectional study surveyed 100 third-semester MBBS students at AIIMS Rishikesh using a validated electronic questionnaire to assess various aspects of their experience with MCQs and EBQs in pharmacology assessments. The study collected data on demographics, stress levels, psychological effects, coping skills and student feedback, while excluding students who were not in the third semester, unwilling to participate or absent during the examination. Results: The study outcome showed no significant difference in scores between MCQs and EBQs. Stress factors during MCQ preparation included academic performance concerns and sleep issues, while course issues and sleep disturbances were primary stressors during EBQ preparation. Suggestions for examination pattern changes were common, indicating students’ desire for support. Conclusion: The study highlights the importance of addressing multifaceted stressors to support student well-being and academic success. Further research is needed to explore effective interventions.